Оригинальные идеи для вязания крючком и спицами - Ращупкина Светлана Юрьевна (РИПОЛ классик, 2010)
Экземпляры: ф.4 (20160715) / Инвентарный номер: 2648 / Цена: / Сис.шифр: 37.248 / Авт.знак: О-65 / ГРНТИ: 75.35 / ББК: 37.248